The use of fuzzy logic for dynamic power control of steam boilers - Lapin, Mykhailo; Sidletskyi, Victor (My University, 2016)
The use of fuzzy logic for dynamic power control of steam boilers it allows the company to save money on buying electricity from supply companies, and receive steam and electricity for their own use purchasing only the main fuel (gas or oil).
Keywords: setpoint; regulator; control; object; fuzzy; динамчне керування; dynamic control; fuzzy logic; steam boilers; парові котли; нечітка логіка; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка